Why Are Pollution Damages Lower in Developed Countries? Insights from High-Income, High-Particulate Matter Hong Kong - Jonathan Colmer; Dajun Lin; Siying Liu; Jay Shimshack (Institute of Labor Economics (IZA), 2021)
Conventional wisdom suggests that marginal damages from particulate matter pollution are high in less-developed countries because they are highly polluted. Using administrative data on the universe of births and deaths, we explore birthweight and mortality effects of gestational particulate matter exposure in high-pollution yet high-income Hong Kong. The marginal effects of particulates on birthweight are large but we fail to detect an effect on neonatal mortality. We interpret our stark mortality results in a comparative analysis of pollution-mortality relationships across studies. We provide early evidence that marginal mortality damages from pollution are high in less-developed countries because they are less developed, not because they are more polluted.
Keywords: Q53; I15; Q56; 330; particulate matter; early childhood; comparative analysis